Information and Analytical Support of Decision-Making Procedures in Strategic Corporate Reengineering - Katsiaryna NAVITSKAYA; Boris ZHALEZKA (Eastern European Journal of Regional Studies)
The results of testing of the instrumental method of multi-agent situational analysis to decision-making of socio-economic development of the region are presented in the paper. Instrumental method includes the technique of multi-agent situational analysis, instrumental and methodical complex, as well as guidelines and usage scenarios to assess and predict the results of socio-economic development of the regions. As a result, the groups of similar regions are identified, the main factors affecting their growth are revealed and recommendations of development are made.